The effects of video modeling and simulation on teaching / learning basic vaulting jump on the vault table - Amri-Dardari, A.; Mkaouer, B.; Nassib, S. H.; Amara, S.; Amri, R.; Ben Salah, F. Z. (Science of Gymnastics Journal, 2020)
The purpose of this study was to compare the effects of different teaching / learning strategies (i.e., verbal feedback, video feedback with modeling, and video feedback with simulation) on performing basic vaulting skills on the vault table. Three male groups of undergraduate students in physical education (i.e., 135 students, divided into 3 groups of 45 subjects) took part in this study. The groups (i.e., traditional, modeling and simulation groups) were divided on equal terms; students are not gymnasts, have the same level and taught by the same teacher. All participants were pretested to determine initial skill level (i.e., direct piked vault). This study covers 24 stoop direct vault sessions, 21 learning and three evaluations spread over 12 weeks (i.e., 2 sessions per week). A video motion analysis (i.e., using Kinovea software) was used to evaluate direct piked vault skills/performance. The results indicate a better improvement of performance in the modeling group compared to the simulation and traditional groups (vault score, 11.80±1.22 pts, 10.85±1.50 pts and 9.01±1.30 pts, respectively with p<0.01). In addition, the analysis of delta-percentage revealed a considerable enhancements of technical performance in the modeling group (46.93%) compared to simulation (27.62%) and traditional (21.64%) groups. In conclusion, video feedback with model`s superposition had led to better learning improvements in vault jump compared with simulation and verbal feedback methods. The video return with the overlay of the model enabled a lot of basic skills learning improvement at the vault table.